Distribution of young's modulus in porcine corneas after riboflavin/UVA-induced collagen cross-linking as measured by atomic force microscopy - Seifert, Jan; Hammer, Christian M.; Rheinlaender, Johannes; Sel, Saadettin; Scholz, Michael; Paulsen, Friedrich; Schäffer, Tilman (PLOS ONE, 2014)
Riboflavin/UVA-induced corneal collagen cross-linking has become an effective clinical application to treat keratoconus and other ectatic disorders of the cornea. Its beneficial effects are attributed to a marked stiffening of the unphysiologically weak stroma. Previous studies located the stiffening effect predominantly within the anterior cornea. In this study, we present an atomic force microscopy-derived analysis of the depth-dependent distribution of the Young's modulus with a depth resolution of 5 µm in 8 cross-linked porcine corneas and 8 contralateral controls. Sagittal cryosections were fabricated from every specimen and subjected to force mapping. The mean stromal depth of the zone with effective cross-linking was found to be 219±67 µm. Within this cross-linked zone, the mean Young's modulus declined from 49±18 kPa at the corneal surface to 46±17 kPa, 33±11 kPa, 17±5 kPa, 10±4 kPa and 10±4 kPa at stromal depth intervals of 0-50 µm, 50-100 µm, 100-150 µm, 150-200 µm and 200-250 µm, respectively. This corresponded to a stiffening by a factor of 8.1 (corneal surface), 7.6 (0-50 µm), 5.4 (50-100 µm), 3.0 (100-150 µm), 1.6 (150-200 µm), and 1.5 (200-250 µm), when compared to the Young's modulus of the posterior 100 µm. The mean Young's modulus within the cross-linked zone was 20±8 kPa (2.9-fold stiffening), while it was 11±4 kPa (1.7-fold stiffening) for the entire stroma. Both values were significantly distinct from the mean Young's modulus obtained from the posterior 100 µm of the cross-linked corneas and from the contralateral controls. In conclusion, we were able to specify the depth-dependent distribution of the stiffening effect elicited by standard collagen cross-linking in porcine corneas. Apart from determining the depth of the zone with effective corneal cross-linking, we also developed a method that allows for atomic force microscopy-based measurements of gradients of Young's modulus in soft tissues in general.
Gesehen am 12.10.2020